I-V response test of 60–150 W mono-crystalline solar panel - Awoyinka, T. D.; David, T. W.; Somefun, T. E.; Somefun, C. T.; Orovwode, H. E. (Frontiers in Energy Research, 2024)
This work elucidated the variations in electrical parameters of mono-crystalline solar panels between Ago-Iwoye weather conditions and the manufacturer's specifications. While manufacturer's specifications for solar panels are based on ideal conditions of 1000 W/m 2 global solar irradiance, AM 1.5, and 25 o C operating temperature, the actual weather conditions at the installation site often differ. This necessitates an investigation into the deviation in electrical parameters of solar panel between the manufacturer's specified parameters and the actual parameters at the installation site. Hence, mono-crystalline (single-crystal) silicon solar panels of 60W, 80W, 100W, and 150W were assessed through the test of current voltage (I-V) response, and the resulting electrical parameters were compared to the manufacturer's specifications. Justifying this deviation at the installation site aids in optimising appropriate solar panel capacity sizing. The test was conducted at an installation site in Ago-Iwoye, Nigeria, and during the test, the four solar panels were exposed to solar irradiance from 11 a.m. to 3 p.m. The results obtained from the I-V and P-V curves revealed that the maximum power output of the four solar panels, which are 60W, 80W, 100W, and 150W, was were 28.6%, 25.9%, 28.9%, and 19.36%, respectively, lower than the manufacturer's specification. Therefore, we recommend adding an additional 20% -30% of the total solar panel capacity during solar PV projects in Agoiwoye localities to ensure appropriate sizing, effective solar power generation, and optimal performance.